The Story of Sir Francis Drake - Elton, Letitia MacColl, 1865-1947; Robinson, T. H. (Thomas Heath), 1869-1954 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Story of Sir Francis Drake" by Mrs. Oliver Elton is a historical account written in the late 19th century. This narrative explores the life and exploits of Sir Francis Drake, a prominent figure in English naval history, particularly known for his role in naval battles against Spain during the age of exploration. The book delves into Drake's motivations, achievements, and challenges as he navigates the treacherous waters of both political intrigue and maritime conflict. At the start of the story, we are introduced to the larger historical context of the time, focusing on the relationship between England and Spain, particularly under the rule of Philip II. The early chapters recount Drake's upbringing in Devonshire, touching upon the tumultuous times of religious conflict in England, which influenced his fierce patriotism and animosity toward Spain and Catholicism. As a child of a Protestant family, he was instilled with a sense of adventure that ultimately led him to the sea. Readers are given insight into the beginnings of his seafaring career, highlighting the hardships he faced, his connections with influential figures like the Hawkins family, and the significant events that paved the way for his later fame. (This is an automatically generated summary.)
Release date is 2022-04-18
D A Alexander and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by University of California libraries)
Keywords: Drake, Francis, approximately 1540-1596 -- Juvenile literature; Explorers -- Great Britain -- Biography -- Juvenile literature; Admirals -- Great Britain -- Biography -- Juvenile literature; Great Britain -- History, Naval -- Tudors, 1485-1603 -- Biography -- Juvenile literature; Great Britain -- History -- Elizabeth, 1558-1603 -- Biography -- Juvenile literature